Efficacy and Safety of Low-Dose Nab-Paclitaxel Plus Tislelizumab in Elderly Patients With Previously Treated Metastatic Non-Small Cell Lung Cancer - Zhu, Wenyu; Geng, Qian; Peng, Haoliang; Jin, Zhihui; Li, Dongqing; Pu, Xiaolin; Wang, Ge; Jiang, Hua (Frontiers in Oncology, 2022)
The combination of immunotherapy and chemotherapy has a synergic effect in non-small cell lung cancer (NSCLC). However, because elderly patients usually have a poor health status and more comorbidities, they are often excluded from clinical trials. We sought to assess the efficacy and safety of low-dose nanoparticle albumin-bound paclitaxel (nab-paclitaxel) plus tislelizumab (an anti-PD-1 antibody) in elderly patients with advanced NSCLC. In this phase 2 clinical trail, eligible patients were those aged ≥65 years with metastatic NSCLC who had disease progression after treatment with ≥1 line of chemotherapy or targeted therapy. Patients with epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) variations were eligible if they demonstrated disease progression after treatment with ≥1 corresponding inhibitor. Primary endpoints were progression-free survival and safety/tolerability. Secondary endpoints included objective response rate and overall survival. Among 29 patients enrolled from May 2019 through August 2020, 21 (72.4%) had adenocarcinoma, 17 (58.6%) had a performance status of 2, 8 (27.6%) had asymptomatic brain metastases, and 13 (44.8%) had EGFR/ALK variations. As of the data cutoff point on April 1, 2021, median progression-free survival and overall survival were 9.5 months and 16.5 months, respectively. Ten patients achieved a partial response (objective response rate of 34.5%). Seventeen (58.6%) patients had ≥1 treatment-related adverse event, with grade 3 events seen in 3 patients (10.3%). The most common adverse events were fatigue (20.7%), fever (17.2%), abnormal liver function (17.2%), and rash (17.2%). These results suggest that low-dose nab-paclitaxel plus tislelizumab is well tolerated and effective in elderly patients with advanced NSCLC, including those with EGFR/ALK variations.